Administrative-Legal Support of Business Entities: New Quarantine Realities - Слободянюк (Журба), Марина Анатоліївна; Слободянюк, Марина Анатоліївна; Слободянюк, М. А.; Слободянюк, Марина Анатольевна; Slobodianiuk, Maryna A.; Жданова, Інна Євгенівна; Жданова, І. Є.; Жданова, Инна Евгеньевна; Zhdanova, Inna Ye.; Матвійчук, Аліна Вікторівна; Матвійчук, А. В.; Матвийчук, Алина Викторовна; et al. (Universidad del Zulia, 2021)
The Covid-19 coronavirus pandemic has affected the world. The government is stepping up quarantine measures in its countries for the second time. Strict quarantine is beginning to be introduced in more and more countries around the world. Quarantine restrictions significantly affect businesses and limit their rights. In this regard, the issue of protection of business rights remains relevant. The purpose of the article is to study the administrative features of protection of the rights of economic entities in quarantine. The subject of the study is the social relations that arise in the protection of business in quarantine conditions. The research methodology consists of the dialectical method, historical method, system method, modeling and abstraction methods, as well as induction, deduction, analysis, synthesis and comparative law methods as a special research methods. The authors came to the conclusion that the state took decisive measures to ensure the rights of economic entities, by they significantly reflected on guarantees for entrepreneurs and in general, in particular, their ability to operate, which significantly affects the economies of countries.

Пандемія коронавірусу Covid-19 вразила світ. Уряд вдруге посилює карантин у своїх країнах. Суворий карантин починає запроваджуватися у все більшій кількості країн світу. Карантинні обмеження суттєво впливають на бізнес та обмежують його права. У зв’язку з цим актуальним залишається питання захисту прав підприємництва. Метою статті є дослідження адміністративних особливостей захисту прав суб’єктів господарювання в умовах карантину. Предметом дослідження є суспільні відносини, що виникають при захисті бізнесу в умовах карантину. Методологія дослідження складається з діалектичного методу, історичного методу, системного методу, методів моделювання та абстракції, а також методів індукції, дедукції, аналізу, синтезу та порівняльно-правового методу як спеціальних методів дослідження. Автори дійшли висновку, що держава вжила рішучих заходів для забезпечення прав суб’єктів господарювання, істотно відбившись на гарантіях підприємців і в цілому, зокрема, на їх працездатності, що суттєво впливає на економіку країн.
Slobodianiuk M. Administrative-Legal Support of Business Entities: New Quarantine Realities / M. Slobodianiuk, I. Zhdanova, A. Matviichuk // Cuestiones Politicas. - Vol. 39. - Iss. 68. - Universidad del Zulia, 2021. - Р. 427-440.
Keywords: legal support; administrative law; pandemic quarantine; legislation; business entities; юридичний супровід; адміністративне право; пандемічний карантин; законодавство; суб'єкти господарювання; Research Subject Categories::LAW/JURISPRUDENCE